2021
DOI: 10.1097/pr9.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs from the mouse tibia fracture model reflect the signature from patients with complex regional pain syndrome

Abstract: Introduction: Complex regional pain syndrome (CRPS) often results from an initial trauma that later produces a disproportionate amount of pain. The mechanisms underlying CRPS have been studied using a tibia fracture model (TFM) in rodents because this model closely mimics symptoms and has several molecular correlates observed in patients with CRPS.Objective: Here, we determined whether the TFM has alterations in circulating microRNAs (miRNAs) and cytokines transported by small extracellular vesicles (sEVs) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Existing studies have linked chronic inflammatory diseases to elevated EV concentrations and altered EV composition [ 50 ]. Some researchers have found that EV concentrations in plasma from a tibia fracture model (closely mimic complex regional pain syndrome), although comparable to controls, are significantly larger in particle size than in control mice [ 51 ]. Studies have found that circulating EV counts are significantly increased in patients with Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS, debilitating disease with multiple symptoms, including pain, depression, and neurocognitive deterioration in function) and that circulating EV counts correlate significantly with serum C-reactive protein levels and have reported that circulating EV counts and EV-specific proteins can be used as novel biomarkers for the diagnosis of ME/CFS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have linked chronic inflammatory diseases to elevated EV concentrations and altered EV composition [ 50 ]. Some researchers have found that EV concentrations in plasma from a tibia fracture model (closely mimic complex regional pain syndrome), although comparable to controls, are significantly larger in particle size than in control mice [ 51 ]. Studies have found that circulating EV counts are significantly increased in patients with Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS, debilitating disease with multiple symptoms, including pain, depression, and neurocognitive deterioration in function) and that circulating EV counts correlate significantly with serum C-reactive protein levels and have reported that circulating EV counts and EV-specific proteins can be used as novel biomarkers for the diagnosis of ME/CFS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miRNAs, most encapsulated in small extracellular vehicles (sEVs) or exosomes, are stable in intercellular communication and may become an original biomarker or risk factor for CRPS ( Ramanathan et al, 2019a ; Wickman et al, 2021 ). Wickman et al (2021) have purified and identified both cytokine and miRNA levels in serum sEVs in a tibia fracture model (TFM) induced-CRPS. The results have shown an unchanged level of cytokines but significantly differential expression of miRNAs.…”
Section: Introduction and Chronic Pain Overviewmentioning
confidence: 99%
“…The most studied EV ncRNAs are miRNAs which are ∼22 nt and negatively regulate gene expression at protein level by either mRNA degradation or translational inhibition [15]. MiRNAs present in circulating EVs have been linked to neurodegenerative disorders and pain [16][17][18][19] and have been proposed as biomarkers for cancer diagnostics, [20][21][22] and for neuropathic injury [1].…”
Section: Introductionmentioning
confidence: 99%